2014
DOI: 10.1002/uog.13223
|View full text |Cite
|
Sign up to set email alerts
|

Fetal lung volume and quantification of liver herniation by magnetic resonance imaging in isolated congenital diaphragmatic hernia

Abstract: Objective To determine associations between fetal lung and liver herniation volumes measured by magnetic resonance imaging (MRI) and mortality/need for extracorporeal membrane oxygenation (ECMO) in cases of isolated congenital diaphragmatic hernia (CDH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
99
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(105 citation statements)
references
References 42 publications
5
99
0
1
Order By: Relevance
“…The mortality rate for fetuses with severe CDH in their study was 52%; ECMO therapy was required in 62% of cases. In patients with mild CDH (total observed-to-expected MR FLV above 32%), mortality rate was only 8% and only 13% of patients needed ECMO therapy [16]. According to Zamora et al [17], a cutoff value of 35% for total observed-to-expected MR FLV yielded a sensitivity of 72% and a specificity of 65% for predicting development of CLD [17].…”
Section: Hagelstein Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…The mortality rate for fetuses with severe CDH in their study was 52%; ECMO therapy was required in 62% of cases. In patients with mild CDH (total observed-to-expected MR FLV above 32%), mortality rate was only 8% and only 13% of patients needed ECMO therapy [16]. According to Zamora et al [17], a cutoff value of 35% for total observed-to-expected MR FLV yielded a sensitivity of 72% and a specificity of 65% for predicting development of CLD [17].…”
Section: Hagelstein Et Almentioning
confidence: 99%
“…Various studies have found that the observed-to-expected MR FLV of both lungs is a reliable prognostic parameter of survival, need for extracorporeal membrane oxygenation (ECMO), and development of chronic lung disease (CLD) [14][15][16][17]. For example, Ruano et al [16] defined severe CDH as total observed-to-expected MR FLV (i.e., in both lungs combined) below 32%.…”
Section: Hagelstein Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…11,20 However, an advantage of antenatal MRI is the identification and quantification of liver herniation which, when combined with observed-to-expected total fetal lung volume, improves prediction characteristics. 17 Thus, MRI may have additional value where available, especially in those cases where the observed-toexpected lung-head ratio on ultrasound shows moderate or severe CDH.…”
Section: Fetal Magnetic Resonance Imaging (Mri) Should Be Used (Wherementioning
confidence: 99%
“…[7][8][9] Studies have shown that the amount of liver herniation can be measured on magnetic resonance imaging and is an independent prognostic factor. [10][11][12] A recent study demonstrated that the amount of liver herniation can be assessed directly on 2-dimensional sonography in the same image that is used to measure the lung-to-head ratio (lung size) by calculating the liver-to-thoracic area ratio. 13 Investigators have also shown that the stomach position in the fetal chest can be considered an indirect method to quantify the degree of liver herniation, which also correlates with prognosis.…”
mentioning
confidence: 99%